An electrochemical γ-C–H arylation of amines in continuous flow. (16th February 2022) - Forni, José A.; Czyz, Milena L.; Lupton, David W.; Polyzos, Anastasios
Graphical abstract: Abstract: Reported here is a regioselective C(sp 3 )–C(sp 2 ) cross coupling reaction between inert γ-C(sp 3 )–H bonds in aliphatic amines and cyanoarenes under electrochemical conditions in flow. The developed methodology takes advantage of a removable redox active auxiliary, which triggers selective 1, 7-hydrogen atom transfer to functionalise an aliphatic C–H bond at the γ-position of an alkyl amine. In this reaction, a cyanoarene radical anion functions as both a selective arylating reagent and a redox active mediator, enabling the controlled one electron reduction of the redox active auxiliary. This strategy offers a new approach towards γ-C(sp 3 )–H bond functionalisation allowing generation of, amongst others, sterically crowded carbon centres under mild reaction conditions and in the absence of additional catalysts or radical initiators.